A Review Study on Small Scale Wind Turbines (International Journal of Innovative Research in Computer Science & Technology, 2021)
Country's growth is inversely proportional  to the quantity of electricity it produces. A country's  economic development should be sustainable if it has the  resources to generate energy continually. Experimental and  numerical research were used to classify vertical axis wind  turbines. Wind turbine arrangement and air acoustic issues  were likewise examined. Examples gained from various  investigations/nations on genuine minuscule breeze turbine  establishment were likewise given. Satisfying future  worldwide energy needs while tending to environmental  change has placed tension on customary power sources. The  wind is one of the potential manageable energy sources. Be  that as it may, since enormous scope wind ranches can  modify environmental conditions, decentralized limited scope wind turbines are a more supportable other option.  This article provides an overview of the many kinds of small scale wind turbines, including horizontal axis and vertical  axis wind turbines. Performance, blade design, and control  are all important factors.
Keywords: Electricity; Generation; Power Source; Turbine; Wind Turbine